Przegląd wybranych portali mapowych prezentujących szlaki rowerowe - Chudziński, Adam; Ławniczak, Radzym (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2023)
This article evaluates map websites that present bicycle routes. Due to the large number of such websites and their highly dynamic development, the analysis was limited to the content presented for the area of Poland. An attempt was made to assess properties like the quality and form of the cartographic message, the legibility of the presented content, the quantity and quality of the accompanying data, and the usability properties. Data from global, national and local portals developed for the voivodship, and even for the city or county, were analysed. The analysis showed that Goole Maps currently offers the best usable properties.